2021
DOI: 10.1007/s12035-021-02508-5
|View full text |Cite
|
Sign up to set email alerts
|

Dolutegravir Inhibition of Matrix Metalloproteinases Affects Mouse Neurodevelopment

Abstract: Dolutegravir (DTG) is a first-line antiretroviral drug (ARV) used in combination therapy for the treatment of human immunodeficiency virus type-1 (HIV-1) infection. The drug is effective, safe, and well tolerated. Nonetheless, concerns have recently emerged for its usage in pregnant women or those of child-bearing age. Notably, DTG-based ARV regimens have been linked to birth defects seen as a consequence of periconceptional usages. To this end, uncovering an underlying mechanism for DTG-associated adverse fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 78 publications
(183 reference statements)
8
26
0
Order By: Relevance
“…Although few studies have addressed placental transfer of CAB and BIC, evidence does suggest that these INSTIs also cross the placental barrier (Pencole et al, 2020;Bukkems et al, 2021;Le et al, 2022). Our previous work investigated pharmacokinetic (PK) and biodistribution (BD) of DTG during pregnancy in mice and confirmed that DTG levels are detectable in brain tissues of embryos following daily oral administration at supratherapeutic dosage (Bade et al, 2021). Our work validated clinical reports of high placental transfer of DTG and was the first to show drug levels in the fetal developing brain during gestation.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Although few studies have addressed placental transfer of CAB and BIC, evidence does suggest that these INSTIs also cross the placental barrier (Pencole et al, 2020;Bukkems et al, 2021;Le et al, 2022). Our previous work investigated pharmacokinetic (PK) and biodistribution (BD) of DTG during pregnancy in mice and confirmed that DTG levels are detectable in brain tissues of embryos following daily oral administration at supratherapeutic dosage (Bade et al, 2021). Our work validated clinical reports of high placental transfer of DTG and was the first to show drug levels in the fetal developing brain during gestation.…”
Section: Discussionsupporting
confidence: 77%
“…Cells were plated at a density of 1 × 10 6 in 12 well plates and treated with phorbol-12-myristate-13-acetate (PMA) for 24 h. This was done to promote cell differentiation to stimulate MMP secretion. Following PMA treatment, cells were treated with DTG, CAB, BIC, or DOX at concentrations of 25, 50, 75, or 100 µM or control vehicle for 24 h. In our previous study, no DTG-induced cytotoxicity was recorded in PMA-stimulated THP-1 cells up to 100 µM ( Bade et al, 2021 ). Thus, for comparative assessments among different INSTIs (DTG, BIC, and CAB) and DOX (positive control) drug concentrations of up to 100 µM were utilized.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations